Comunidade de aves em áreas campestres degradadas por cultivos, em processo de restauração no bioma pampa, sul do Brasil - Silva, Thaiane Weinert da (2019)
Bird community in degraded grassland areas by crops, in restoration process in the Pampas biome, south of Brazil. Conversion of natural habitats due to other land uses has focused on ecological restoration, which is aimed to recover degraded ecosystems. Degradation of native habitats also occur in Pampas biome grasslands in Rio Grande do Sul, which comprise 63% of its area and much of its use is destined to agriculture. The objectives of this study were evaluate the structure and composition of the bird communities in passive and active restoration sites of southern Brazil. We also relate them to vegetation variables, and verify the influence of the remnats grasslands of the landscape surrounding the restoration sites. This is the first study of restoration evaluating the bird community realized in these grasslands and in the southeastern South America. Four passive restoration sites and one active which previously had crops were compared to reference areas, i.e. native grasslands. Bird communities were sampled from 2015 to 2017 in point counts of 5 min and 100-m radius. The vegetation variables – height, degree of visual obstruction and soil cover – were surveyed through five plots at each point count of birds. We used community analysis packages from R software for the estatistical analyzes, and QuantumGIS for the landscape analyzes. We did not found significant differences in species richness, abundance and composition of bird communities between passive restoration and reference areas, and the number of bird species associated to grasslands were also similar. Seven species responded significantly to the grassland type, survey year, vegetation height, low grasses and/or herbs presence. In addition, eight species recorded are globally or regionally threatened, three of them exclusive to the restoration sites. In the active restoration site, after three consecutive years of monitoring, bird species richness and abundance were higher than the reference area, and species composition also differed in both sites. Six vegetation attributes were different between active restoration and reference area, but in the third year of monitoring grasses and herbaceous became more similar to the native grassland. As for landscape analysis, we found species richness, abundance and occurrence of eight species analyzed individually did not show significant relationship with the amount of the native grasslands remnants surrounding the restoration sites. With caution to extrapolate the results due to the maximum number of replicates that were possible, it was possible to conclude that both passive and active restoration can be used for the bird conservation, since they seem to provide suitable habitat structure for the grassland birds. It is also important consider the surrounding landscape matrix, which can influence the restoration process. Futher studies involving the restoration of degraded habitats and long-term efforts are recommended, evaluating not only plants as tradicionally accomplished, but also animals, providing more consistent and applicable, as well as complementary information.